Body composition and anaerobic exercise capacity in elite adolescent track athletes - Kim, S.-H.; Park, K.-J. (Trends in Sport Sciences, 2025)
Introduction: Relative age significantly impacts adolescent track athletics. Therefore, identifying and developing adolescent athletes to compete effectively in track events is essential.